2022
DOI: 10.1109/tbme.2022.3156018
|View full text |Cite
|
Sign up to set email alerts
|

An EMG-Assisted Muscle-Force Driven Finite Element Analysis Pipeline to Investigate Joint- and Tissue-Level Mechanical Responses in Functional Activities: Towards a Rapid Assessment Toolbox

Abstract: Joint tissue mechanics (e.g., stress and strain) are believed to have a major involvement in the onset and progression of musculoskeletal disorders, e.g., knee osteoarthritis (KOA). Accordingly, considerable efforts have been made to develop musculoskeletal finite element (MS-FE) models to estimate highly detailed tissue mechanics that predict cartilage degeneration. However, creating such models is time-consuming and requires advanced expertise. This limits these complex, yet promising, MS-FE models to resear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 81 publications
0
58
0
Order By: Relevance
“…However, since marker-based motion analysis are reported to be inaccurate in estimating knee secondary kinematics during dynamic activities [51], the knee's extra DoFs for all the MS models were either locked (e.g., abduction/adduction and internal/external rotations) or defined as a function of the knee flexion angle (e.g., tibiofemoral translations and patella DoFs) [50], [52]. Importantly, previous studies, including ours on the development of the current workflow [21], [36], [37], [53], have shown that a 12 DoFs FE knee model driven by a 1 DoF knee EMG-assisted MS model is capable of estimating knee joint kinetics, secondary kinematics, and tissue mechanics consistent with in vivo data and those of a similar FE model when driven by a 12 DoFs knee MS model. Likewise, it has been reported that muscle activation patterns, as used in the current study to inform the MS analyses, are directed to effectively stabilize knee abduction/adduction moment and well estimate JCFs even when using an MS model with a 1 DoF knee joint [54].…”
Section: B Musculoskeletal Analysesmentioning
confidence: 95%
See 4 more Smart Citations
“…However, since marker-based motion analysis are reported to be inaccurate in estimating knee secondary kinematics during dynamic activities [51], the knee's extra DoFs for all the MS models were either locked (e.g., abduction/adduction and internal/external rotations) or defined as a function of the knee flexion angle (e.g., tibiofemoral translations and patella DoFs) [50], [52]. Importantly, previous studies, including ours on the development of the current workflow [21], [36], [37], [53], have shown that a 12 DoFs FE knee model driven by a 1 DoF knee EMG-assisted MS model is capable of estimating knee joint kinetics, secondary kinematics, and tissue mechanics consistent with in vivo data and those of a similar FE model when driven by a 12 DoFs knee MS model. Likewise, it has been reported that muscle activation patterns, as used in the current study to inform the MS analyses, are directed to effectively stabilize knee abduction/adduction moment and well estimate JCFs even when using an MS model with a 1 DoF knee joint [54].…”
Section: B Musculoskeletal Analysesmentioning
confidence: 95%
“…Hence, the OpenSim API for MATLAB and scaled models (i.e., 15 MS models in total) were used to execute inverse kinematics, inverse dynamics (to calculate knee external moments), and SO-based muscle force estimation. Then muscle moment arms, muscle-tendon lengths, and tibiofemoral and patellofemoral JCFs were calculated using OpenSim analysis toolbox via the API (i.e., muscle analysis and joint reaction tools, respectively) [36]. Muscle moment arms and muscle-tendon lengths were calculated to be used as input to the EMG-assisted MS model (section II.B.2), and later to calculate the corresponding inputs for the FE models of the study (section II.C.2) (Fig.…”
Section: B Musculoskeletal Analysesmentioning
confidence: 99%
See 3 more Smart Citations